METHODS OF ASSESSMENT AND THERAPEUTIC STRATEGIES FOR MANAGING PATIENTS WITH COMORBIDITY OF BLAST-RELATED INJURIES AND POST-TRAUMATIC STRESS DISORDER (Psychology Travelogs, 2025)
The article examines current approaches to the diagnosis and treatment of patients with comorbidity of blast-related traumatic brain injury (bTBI) and post-traumatic stress disorder (PTSD), which represent one of the most pressing issues in contemporary military medicine and psychiatry. The high prevalence of blast trauma among military personnel, particularly in the context of ongoing armed conflicts, has significantly increased the number of individuals experiencing both organic brain injuries and severe psychological trauma. The coexistence of bTBI and PTSD complicates clinical evaluation, since cognitive impairments, emotional instability, and sleep disturbances may be attributed either to neurological damage or to psychiatric pathology. This overlap requires the implementation of advanced diagnostic criteria, psychometric instruments, and neuroimaging techniques to ensure accurate differentiation and timely intervention. The study highlights the importance of structured clinical interviews such as CAPS-5 and HADS for assessing the psychological state of patients, alongside psychometric tools including the Connor-Davidson Resilience Scale (CD-RISC) and the SF-36 Health Survey to evaluate resilience and quality of life. Special attention is devoted to instrumental diagnostics, with magnetic resonance imaging (MRI) used to detect microstructural brain changes, functional MRI (fMRI) applied to study alterations in cognitive networks, and electroencephalography (EEG) utilized to register pathological brain activity patterns associated with PTSD and TBI. In addition, biological markers such as IL-6, TNF-α, and S100B are discussed as promising objective indicators of neuroinflammation and oxidative stress, providing new opportunities for prognostic assessment and individualized therapeutic planning. The article further analyzes the relationship between the severity and localization of blast injuries and the intensity of PTSD symptoms, emphasizing that even mild injuries may be associated with severe psychological consequences. Both classical rehabilitation methods cognitive behavioral therapy and EMDR – and innovative strategies-virtual reality therapy and neurofeedback – are evaluated for their effectiveness in reducing PTSD symptoms and improving cognitive functioning in affected soldiers. Finally, the study underscores the critical importance of a multidisciplinary approach, integrating neurologists, psychiatrists, psychologists, and rehabilitation specialists, to provide comprehensive care and facilitate the reintegration of veterans into civilian life.
Keywords: mine-blast trauma; post-traumatic stress disorder; diagnostics; psychometric tools; MRI; biomarkers; rehabilitation; multidisciplinary approach